PENDEKATAN DAN TEKNIK SUPERVISI DI ERA DIGITALISASI DALAM MENINGKATKAN PROFESIONALISME DAN MUTU PENDIDIKAN - Kusmanto, Adi; Syaihul Anwari, Muhammad; Zuhri , Syaefuddin (Al Fattah Ejournal Sma Al Muhammad Cepu, 2024)
Supervision is an important component in efforts to improve learning achievement and teacher quality, professional teachers will produce good education outputs, this study examines supervision models, approaches and techniques for implementing supervision in the digitalization era. Data sources are obtained from library studies, articles, books, readings and other sources:   In the era of digitalization, supervisors must have and master professional aspects such as competence, leadership, character, communication skills, creativity, and commitment so that supervision can run optimally. In the practice of educational supervision, it must be carried out consistently and routinely, several approaches in educational supervision can be applied in carrying out supervision, namely direct, indirect, and collaborative approaches. A supervisor needs to understand various supervision models as a basis for knowledge and skills to carry out their supervisory duties.  Each supervision model has its own characteristics, so its use must be in accordance with the target being supervised so that supervision can take place effectively and efficiently.